Reformulasi Diversi Dalam Undang-Undang Nomor 11 Tahun 2012 Sebagai Upaya Perlindungan Anak - Muhammad Ridho Sinaga; Somawijaya Somawijaya; Agus Takariawan (Faculty of Law, Andalas University, 2021)
Discussing that children is very important. The Protection of children in a nation's society is a benchmark for the nation's civilization itself. Therefore, all elements of society and components of the nation must strive so that children do not commit crimes or other disgraceful acts. Diversion efforts are carried out in every legal process by law enforcers, the Police, the Public Prosecutor, and the Court. In practice, diversion has not been tested for its effectiveness for 3 parties. This study examines the concept of diversion in the juvenile criminal justice system in Indonesia and diversion reformulation that reflects the principle of child protection. The method used in this research is descriptive analysis. The purpose of this study was to determine the concept of diversion in the juvenile criminal justice system in Indonesia and to reformulate diversion that reflects the principle of child protection. The results of this study are, the concept of diversion in the juvenile criminal justice system in Indonesia is a concept by diverting a case from a formal process to a non-formal process. The main principle of implementing the concept of diversion, namely persuasive action or a non-penal approach that provides an opportunity for someone (especially child) to correct mistakes and become a good person again. Reformulation of law enforcement against criminal acts committed by children should be carried out, of course by reforming the criminal law by revising regulations and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, especially regarding diversion requirements, in the provisions of article 7 paragraph (2) letter (a) Law no. 11 of 2012 concerning Juvenile Justice System, with Article 9 paragraph (2).